Diagnosis as a Naming Ceremony: Caution Warranted in Use of the DSM-IV with Canadian Aboriginal Peoples - Overmars, Danika (First Peoples Child & Family Review, 2010)
The Diagnostic and Statistical Manual of Mental Disorders, 4th is the primary tool for diagnosis of mental disorders used in the field of mental health. Despite the widespread use of the DSM-IV there are limits to its applications, particularly with Canadian Aboriginal people. This paper draws parallels between the process of diagnosis and an Aboriginal naming ceremony used by the Coast-Salish people in British Columbia. Caution is suggested when applying Western based diagnoses to Aboriginal people due to the lack of cultural relevance and recommendations are made for appropriate use. Edition (DSM-IV; APA, 1994)